PERAN MUSEUM SEJARAH AL-QUR’AN SUMATERA UTARA DALAM MELESTARIKAN WARISAN ISLAM - Solin, Sefty Marchella; Secelia Oktayeni Simamora; Fadhilah Syahputri (STKIP Subang, 2026)
Abstract: The Museum of Qur'an History of North Sumatra is one of the important facilities in preserving Islamic heritage in Indonesia. The existence of this museum functions not only as a place to store historical artifacts but also as an educational medium for the public regarding the history, writing, and development of the Qur'an over time. This article aims to identify and describe the role of the Museum of Qur'an History of North Sumatra in preserving Islamic heritage. The method used in this study is a literature review by examining various relevant sources. The results show that the museum plays a role as a center of education, preservation of history, and a religious tourism facility that provides benefits to the community in increasing understanding and love for the Qur'an. Therefore, the museum has a significant contribution in maintaining Islamic values in the modern era.